Prevalence of the Complications of Diabetes in Developing Countries - C, Sarpong; K, Nsiah; O, Mensah F.; E, Agyeman-Duah; D, Ahmed F. (Archives of Clinical and Biomedical Research, 2017)
Diabetes mellitus is a medical condition which arises when there is an uncontrollably high level of glucose in the blood. It is a carbohydrate metabolism disorder which also affects protein and fatty acid metabolisms. Several complications result from diabetes as a result of poor glycemic control. This project aimed at determining the various complications developed by diabetics who visited the Diabetics Clinic of the Komfo Anokye Teaching Hospital (KATH), Kumasi, Ghana, from January to December, 2013. It involved 475 diabetes with an age range of 11 to 100 years with modal age range being greater than 60 years (56.8%) and a mean age of 63.8 ± 3.2 years. It comprised of 45.7% males and 54.3% females. The predominant diabetes type was type 2 (affecting 269 patients) followed by unclassified diabetes type (affecting 188 patients) and then type 1 diabetes (also affecting 18 patients). Complications were found in 365 (76.8%) patients with most of these complications occurring in females who were above 40 years. The most prevalent complication was hypoglycemia, which affected 180 patients (37.9%). Peripheral circulatory complication affected 18 patients (3.8%), renal complication affected 123 patients (25.9%) and ketoacidosis also affected 42 patients (8.8%) whilst two patients (0.4%) suffered multiple complications. These complications caused 57 deaths (12%) and these deaths were most prevalent in unclassified diabetes.